On the Approximate Evaluation of Interaction of Cracks in Elastic Media - Sokołowski, M.; Turska-Kłębek, E. (Engineering Transactions, 1983)
A method of approximate analysis is presented concerning the state of stress, and the stress intensity factors in particular, in elastic media subject to a plane state of strain and containing arbitrary arrays of cracks. In the case when ·the crack distribution is not too dense, the method proposed makes possible the determination of the required stress parameters in a manner resembling that used in solving the statically indeterminate systems of structural mechanics.